1991
DOI: 10.1136/gut.32.12.1514
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological evaluation of colonic mucosal biopsy specimens in chronic inflammatory bowel disease: diagnostic implications.

Abstract: In a prospective blind evaluation of multiple colonic mucosal biopsy specimens, 45 clinically well defined patients with chronic inflammatory bowel disease (21 Crohn's disease and 24 ulcerative colitis) and 16 control subjects (seven normal subjects and nine patients with diverticular disease) were studied to identify reproducible histopathological features which could distinguish chronic inflammatory bowel disease (CIBD) from non-CIBD and Crohn's disease from ulcerative colitis. Using kappa statistics 16 of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
121
1
21

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(149 citation statements)
references
References 30 publications
6
121
1
21
Order By: Relevance
“…Leirisalo-Repo et al (20) reported the presence of histologic lesions in the colon or ileum in 50% of patients with rheumatoid arthritis (RA) and 28% of "controls." Some of these differences are almost certainly due to subjective interpretation of subtle histologic abnormalities (22); however, the demonstration of a high prevalence of colonic inflammation in SpA and ileocolonic abnormality in RA (19,20,23) cannot be explained on these grounds and requires alternate explanation.…”
Section: Spa and Intestinal Diseasementioning
confidence: 99%
“…Leirisalo-Repo et al (20) reported the presence of histologic lesions in the colon or ileum in 50% of patients with rheumatoid arthritis (RA) and 28% of "controls." Some of these differences are almost certainly due to subjective interpretation of subtle histologic abnormalities (22); however, the demonstration of a high prevalence of colonic inflammation in SpA and ileocolonic abnormality in RA (19,20,23) cannot be explained on these grounds and requires alternate explanation.…”
Section: Spa and Intestinal Diseasementioning
confidence: 99%
“…Structural epithelial changes include the presence of an irregular surface, sometimes called pseudovillous or villiform surface and a disturbed crypt architecture. [72][73][74] Atypical presentations such as ulcerative colitis with left-sided colitis and peri-appendicular inflammation or caecal patch are occasionally observed. However, the major clinical conditions where endoscopic and histological lesions may not be characteristic include initial onset of the disease, inflammatory diarrhoea in children, patients with liver disease and IBD, patients under treatment and patients presenting with severe, fulminant disease.…”
Section: Inflammatory Conditionsmentioning
confidence: 99%
“…Similar findings were also obtained by Seldenrijk, (1991) and Berre et al, (1995) who found that the mean age for UC was 40 years and 39 years respectively, but the opposite was detected for sex predominance as they found that men were affected more often than women. (17,18,19).…”
Section: B a A B C Dmentioning
confidence: 99%